The influence of selected sociodemographic data on coping with stress by parents of hospitalized children - Starczewska, Małgorzata Elżbieta; Wałdoch, Anna; Reczyńska, Anna; Augustyniuk, Katarzyna; Stanisławska, Marzanna; Grochans, Elżbieta (Family Medicine & Primary Care Review, 2017)
Background. A child’s illness is a major stress-inducing factor for parents. It alters interpersonal relationships in and outside the family unit and weakens the sense of safety. In stressful situations, everyone adopts certain behaviors that are defined as a stress-coping style. Objectives . The aim of the study was to analyze factors which contribute to the choice of a stress-coping style by parents of hospitalized children. Material and methods . This survey-based study was conducted among 292 parents of children hospitalized in the General and Neurological Pediatric Ward of the Voivodeship Independent Public Hospital in Gorzow Wielkopolski. The research instruments were: the Coping Inventory for Stressful Situations (CI SS) – a standard questionnaire for measuring one’s ability to cope with difficult situations, developed by N. S. Endler & J. D. A. Parker, and a questionnaire of the authors’ own design. Results . The parents of hospitalized children employed all types of stress-coping strategies, but task-oriented coping was the most common (41.10%). Education was the only sociodemographic factor that had a statistically significant influence on the parents’ choices of stress-coping styles (p < 0.01). Conclusions . 1. Most frequently, parents of ill and hospitalized children adopt a task-oriented coping style. 2. Parents’ education significantly contributes to their choice of a stress-coping style.